2004
DOI: 10.1002/bjs.4516
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the survival of patients with peritoneal carcinomatosis of colorectal origin treated by aggressive cytoreduction and hyperthermic intraperitoneal chemotherapy

Abstract: The survival of patients with peritoneal carcinomatosis of colorectal origin is dominated by the extent of disease and the amount of residual tumour after cytoreduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 23 publications
7
134
0
5
Order By: Relevance
“…After resection, the completeness of cytoreduction (cc) 27,29,55 is evaluated using the cc score (Table v).…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…After resection, the completeness of cytoreduction (cc) 27,29,55 is evaluated using the cc score (Table v).…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…In contrast, rectal cancer patients having the same treatments had a median survival of 17 months and there were no longterm survivors [10]. Verwaal showed that the prognosis of rectal cancer patients treated for peritoneal metastases was markedly reduced (p = 0.069) [7]. A similar phenomenon was reported by Yang et al in the prospective randomized trial of gastric cancer patients treated with CRS and HIPEC for peritoneal metastases.…”
Section: Prior Surgical Score (Pss)mentioning
confidence: 55%
“…Verwaal and colleagues reported 15 patients with signet ring cells had a median survival of 13.0 months as compared to 86 patients without signet ring cells identified in peritoneal metastases had a survival of 21.4 months (p = 0.008). These authors recommended that signet ring cells in peritoneal metastases are a relative contraindication to the use of CRS and HIPEC to treat peritoneal metastases in colon cancer patients [7]. Also, it is well established that signet ring cells carry a poor prognosis in patients with gastric cancer.…”
Section: Histopathology Including Lymph Node Statusmentioning
confidence: 99%
“…There were no five-year survivors in the rectal cancer group as compared to 30 in the colon cancer group [16]. Verwaal showed in a multivariate analysis of 102 patients that peritoneal metastases treated with CRS and HIPEC had a poorer prognosis (p=0.069) [17].…”
Section: Modification Of Primary Rectal Cancer Surgery In Patients Wimentioning
confidence: 96%